Traditional Chinese Medicine nursing experience of a patient undergoing vitrectomy for diabetic retinopathy (1例糖尿病性视网膜病变患者玻璃体切割术后中医护理体会) - XING Hui (兴慧); YIN Kexin (尹可欣); DUAN Yixuan (段怡璇); LI Jinhuan (李金环) (中西医结合护理)
Diabetic retinopathy is an ophthalmic disease, a complication of diabetes, with a high incidence, affecting patients' daily life and reducing their quality of life. Patients with diabetic retinopathy are often treated with surgery, such as vitrectomy. This paper summarized the Traditional Chinese Medicine nursing experience of a patient undergoing vitrectomy for diabetic retinopathy, including emotional care, dietary care, ophthalmologic care and so on. Nursing interventions by syndrome differentiation were carried out to relive the clinical symptoms and improve the rehabilitation of the patient (糖尿病性视网膜病变为眼科疾病, 属于糖尿病并发症, 发病率较高, 严重影响患者日常生活。玻璃体切割术是临床治疗该病的常用方法。本文总结1例糖尿病性视网膜病变患者玻璃体切割术后的中医护理经验, 包括情志护理、饮食护理、体位护理、眼科护理等, 通过辨证施护, 达到改善患者症状, 促进疾病康复的目的。)